STORIES IN TEACHING LANGUAGE - Shakhodat Rakhmatullaeva Quranbay qizi (Research Focus International Scientific Journal, 2024)
This article explores the efficacy of integrating storytelling into language teaching methodologies. Drawing upon diverse theoretical frameworks, it examines the role of narratives in facilitating language acquisition and cultural understanding. Through a review of existing literature and empirical evidence, the article elucidates the cognitive and socio-cultural benefits of utilizing stories as pedagogical tools. Practical strategies for implementing narrative-based approaches in language classrooms are delineated, catering to various proficiency levels and linguistic contexts. Ultimately, this research underscores the transformative potential of stories in enriching language education paradigms, fostering engagement, and nurturing intercultural competence among learners.